Observations on the in vitro Effects of Chylomicra, Low-Density Lipoproteins and Phospholipids on Human Plasma Euglobulin Lysis - Pappenhagen, Albert R; Koppel, J. L; Olwin, John H (Thrombosis and Haemostasis, 1963)
Data have been presented on the in vitro effects of human chylomicra, low-density human plasma lipoproteins, and partially purified preparations of various phospholipids on human plasma euglobulin lysis. Euglobulin lysis was found to be accelerated by preparations of mixed soybean phospholipids (aso-lectin), cephalin, phosphatidyl inositol, phophatidyl serine and phosphatidyl ethanolamine. In contrast, it was found to be inhibited by preparations of human chylomicra, low-density human plasma liproproteins and lecithin. Inhibition of euglobulin lysis produced by any of these three agents could be diminished or completely overcome by the simultaneous presence of suitable levels of any one of the accelerating agents. In all cases studied, both inhibitory and accelerating effects were observed to be concentration-dependent. Evidence has been obtained to suggest that in the case of the accelerating agents the observed increased rate of euglobulin lysis is not a direct effect on lysis itself, but rather is due to more complete precipitation of plasminogen in the presence of these substances. On the other hand, it appears that the inhibitory effects observed are not related to the extent of plasminogen precipitation, but are actually true inhibitions of euglobulin lysis. The possible clinical significance of some of these observations has been briefly discussed.